Reliability analysis of the Musical Communicativeness Scale (Per Musi, 2021)
The Musical Communicativeness Scale was developed through research carried out in the United States of America in the 1960s. Since then, it has been used to assess behavior based on sound and musical stimuli. In Brazil, it was submitted to validate studies with positive results. This study aimed to verify its reliability in two approaches to music therapy. Hence, 5 examiners analyzed 24 excerpts of videos, being 12 excerpts from consultations in Music Centered Music Therapy and 12 excerpts from videos in Neurological Music Therapy. Subsequently, the Spearman Correlation Test was performed. The results showed moderate and strong correlations, indicating evidence of reliability for this scale.